PsrA is a novel regulator contributes to antibiotic synthesis, bacterial virulence, cell motility and extracellular polysaccharides production in Serratia marcescens. Issue 1 (10th December 2021) - Pan, Xuewei; Tang, Mi; You, Jiajia; Osire, Tolbert; Sun, Changhao; Fu, Weilai; Yi, Ganfeng; Yang, Taowei; Yang, Shang-Tian; Rao, Zhiming
Abstract: Serratia marcescens is a Gram-negative bacterium of the Enterobacteriaceae family that can produce numbers of biologically active secondary metabolites. However, our understanding of the regulatory mechanisms behind secondary metabolites biosynthesis in S. marcescens remains limited. In this study, we identified an uncharacterized LysR family transcriptional regulator, encoding gene BVG90_12635, here we named psrA, that positively controlled prodigiosin synthesis in S. marcescens . This phenotype corresponded to PsrA positive control of transcriptional of the prodigiosin-associated pig operon by directly binding to a regulatory binding site (RBS) and an activating binding site (ABS) in the promoter region of the pig operon. We demonstrated that L-proline is an effector for the PsrA, which enhances the binding affinity of PsrA to its target promoters. Using transcriptomics and further experiments, we show that PsrA indirectly regulates pleiotropic phenotypes, including serrawettin W1 biosynthesis, extracellular polysaccharide production, biofilm formation, swarming motility and T6SS-mediated antibacterial activity in S. marcescens . Collectively, this study proposes that PsrA is a novel regulator that contributes to antibiotic synthesis, bacterial virulence, cell motility and extracellular polysaccharides production in S. marcescens and provides important clues for future studies exploring the function of the PsrA and PsrA-like proteins which are widely present in many other bacteria.